Workshop Digital Branding UMKM Desa Gajahan, Colomadu, Karanganyar - Dwi Retnoningsih; Revika Anastasya; Leni Andani; Malik Fajar Sidik; Desy Triastuti (Universitas Veteran Bangun Nusantara, 2024)
Digital branding has become a crucial tool for the development of MSMEs in the digital era. This community service activity aims to enhance the understanding and skills of digital branding among MSME practitioners in Gajahan Village, Colomadu Subdistrict, Karanganyar Regency. Through a series of workshops and direct mentoring, participants were taught how to effectively utilize digital platforms such as social media to promote their products. A qualitative method was employed in this study to evaluate the impact of the activity, with data collected through in-depth interviews, observations, and evaluation. The findings indicate a significant improvement in participants' understanding of digital branding concepts and techniques, as well as their ability to implement digital marketing strategies. The strength of this activity lies in delivering practical knowledge that is directly applicable by MSMEs, despite challenges in technology adaptation and limited resources. This activity also highlighted the great potential for further development through continuous training and local government support. It is hoped that this activity model can be replicated for MSME development in other regions, to accelerate digital transformation and enhance their competitiveness in the global market. Keywords: Digital Branding, MSMEs, Training, Gajahan Village, Digital Marketing